2014
DOI: 10.1016/j.biotechadv.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Natural products from resurrection plants: Potential for medical applications

Abstract: Resurrection species are a group of land plants that can tolerate extreme desiccation of their vegetative tissues during harsh drought stress, and still quickly - often within hours - regain normal physiological and metabolic functions following rehydration. At the molecular level, this desiccation tolerance is attributed to basal cellular mechanisms including the constitutive expression of stress-associated genes and high levels of protective metabolites present already in the absence of stress, as well as to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(48 citation statements)
references
References 126 publications
0
47
0
1
Order By: Relevance
“…Moreover, the level of maltotriose in 'Shami' leaves is much higher in the S-AR, which may indicate its involvement in the plant responses to abiotic stresses. Melezitose is reported to exist in high level upon stress (Martinelli et al, 2013) and correlates well with the level of desiccation tolerance (Gechev et al, 2014).…”
Section: Shami @Trmentioning
confidence: 87%
“…Moreover, the level of maltotriose in 'Shami' leaves is much higher in the S-AR, which may indicate its involvement in the plant responses to abiotic stresses. Melezitose is reported to exist in high level upon stress (Martinelli et al, 2013) and correlates well with the level of desiccation tolerance (Gechev et al, 2014).…”
Section: Shami @Trmentioning
confidence: 87%
“…This is for the most part achieved by the presence of efficient antioxidant systems. It is thus not surprising that resurrection plants have highly efficient antioxidant systems, which in turn have been proposed to be a valuable source of antioxidant potential for biotechnological applications both in plant stress tolerance as well as in the medicinal and cosmetic markets (Toldi et al 2009;Gechev et al 2014). Studies have shown that these comprise use of 'housekeeping' antioxidants (Illing et al 2005), often presenting unusual characteristics at low plant water contents (Farrant et al 2007(Farrant et al , 2012, as well as antioxidants such as 1-and 2-cys-peroxiredoxins, glyoxylase I family proteins, metallothionine-like antioxidants, oxidoreductases, several members of the aldehyde-dehydrogenases, and various polyphenols that are not typically highly expressed during dehydration of desiccation-sensitive material (reviewed in Farrant et al 2012Farrant et al , 2015Dinakar and Bartels 2013).…”
Section: Desiccation-tolerant Extremophytesmentioning
confidence: 99%
“…Recently, several studies have reported that some agents that are currently used to promote immunity may also inhibit tumour growth (7)(8)(9). Research into the activity of natural products and their potential for as cancer treatments is therefore of great medical importance (10,11).…”
Section: Introductionmentioning
confidence: 99%